Can the land rental market facilitate smallholder commercialization? Evidence from northern Ethiopia - Menasbo Gebru; Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
The paper utilizes household panel data to investigate whether the land rental market can facilitate improved access to land for land-poor tenant households over time and thereby facilitate expansion of their farming activity. The paper utilizes data 8-17 years after land certification to assess the long-term effect of land certification on the allocative efficiency in the land rental market in areas where land certification stimulated land renting in the early years after certification. The paper uses three rounds of balanced panel data collected from 320 smallholder farmers in 2006, 2010 & 2015 from rural Tigrai, northern Ethiopia. Random effects dynamic probit and Tobit models were used to assess factors that may explain access, participation, and intensity of participation on the tenant side of the tenancy market. Tenants' access to land was found to be severely constrained. Previous access and participation had strong positive effect on access and participation and intensity of participation in later periods. Non-convex transaction costs and entry barriers, therefore, appear as severe constraints towards the land rental market facilitating smallholder commercialization through tenancy access to land. More active land rental market coordination interventions are needed to boost the land rental market as a vehicle for facilitation of smallholder commercialization.
Keywords: Q15; 330; Land rental market; tenants' land access; dynamic probit; dynamic tobit; Tigrai; Ethiopia